Application of Fuzzy Control and IoT Monitoring on Small Scale Biofermentor for Making Virgin Coconut Oil - Ayusari, Ayusari; Abdul, Waris; Muhammad Tahir, Sapsal (Salaga Journal, 2024)
Virgin Coconut Oil is a pure coconut oil that can be obtained from the extract of fresh and old coconut meat. This study aimed to evaluate the performance of a biofermentor integrated with a fuzzy logic control system and IoT for VCO production. The research involved designing control rules to regulate temperature, testing the IoT system for real-time monitoring, and assessing the biofermentor's performance. The parameters observed were control system response, temperature, yield and moisture content.  Results showed that the fuzzy control system effectively maintained temperature stability, resulting in a higher yield (39.65%) and lower moisture content (0.08%) compared to conventional methods. In addition, the fuzzy control rules are able to regulate the power so that the temperature overshoot is quite small (1%), the settling time is relatively short (9 minutes), the temperature is stable, and the steady state error is 1.02% (with in tolerance limits).